(untitled) (PERcursos Linguísticos, 2021)
We address an analytical approach of video games that may take into account its practical dimension, considering them as language objects put in action as an enunciative praxis. Given that video game are an interactive media, we must infer the response of a player, therefore establishing yet an interpretative praxis, that composes a complex structure for the major practice. The practice starts with an enunciation that address the player with task to complete, then houses the development of those tasks and the performance evaluation. To demonstrate such structure, we recur to Jacques Fontanille’s proposes relating to Semiotics of Culture, as a notable author in Discursive Semiotics’ field and its interfaces with Anthropology, Sociology and Phenomenology.